The Mystery of the Blue Train [large type] : A Hercule Poirot Mystery - Christie, Agatha, 1890-1976 (Christie, Agatha, 1890-1976. Hercule Poirot mysteries., 2014)
"The luxurious Blue Train carries its passengers across France, from dreary wintertime England to the sunny French Riviera. When it arrives at Nice, a guard attempts to wake serene Ruth Kettering from her slumber. But she will never wake again -- she has been killed, and a heavy blow has disfigured her features almost beyond recognition. What is more, her precious rubies are missing and her ever-present maid was dismissed from the train back in Paris. Was it a crime of passion, or a bold train robber? The French police think a robber is the most plausible solution. Yet Hercule Poirot is not convinced, so he stages an eerie reenactment of the journey, complete with the murderer on board..." --Cover, p. 4.